Boron quantum dot and starch carbon compound as well as preparation method and application thereof

Through the preparation of boron quantum dots and starch carbon composites, a composite with high lithium ion adsorption capacity is formed, which solves the problem of insufficient lithium storage capacity and cycling performance of the negative electrode materials of existing lithium ion batteries, and achieves better electrochemical performance and long life.

CN119833622APending Publication Date: 2025-04-15ZHONGBEI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510170230.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The lithium storage capacity and circulation performance of existing lithium-ion battery anode materials are insufficient, making it difficult to meet the needs of high energy density and long life.

Method used

Boron quantum dots and starch carbon composites are used as negative electrode materials, and prepared by hydrothermal reaction and high-temperature annealing to form a composite with a wrinkled spherical structure to improve the adsorption capacity of lithium ion.

Benefits of technology

It achieves good lithium storage capacity and electrochemical performance, especially under high current testing conditions, long cycle performance and rate performance are better than traditional starch carbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833622A_ABST
    Figure CN119833622A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion battery negative electrode materials, in particular to a boron quantum dot and starch carbon compound and a preparation method and application thereof. The preparation method of the boron quantum dot and starch carbon compound provided by the invention comprises the following steps: mixing starch and ammonium pentaborate, adding the mixture into a boron quantum dot solution, stirring, then carrying out hydrothermal reaction, and finally drying and annealing to obtain the boron quantum dot and starch carbon compound. Wherein the mass ratio of the starch to the ammonium pentaborate is 1: (0.3-1). The boron quantum dot and starch carbon compound provided by the invention has relatively good lithium storage capacity, the long cycle performance and rate capability under a large-current test condition are superior to those of a starch carbon material, the improvement of electrochemical performance is realized, and the application range of the boron quantum dot is further expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a boron quantum dot and starch-carbon composite, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are currently widely used in energy storage, power batteries and other fields, but the negative electrode material currently used in lithium-ion batteries is mainly graphite, and the theoretical lithium storage capacity of graphite is only 372mAh / g, which limits the development of the negative electrode lithium storage capacity.

[0003] Biomass carbon materials have attracted widespread attention due to their low cost, wide variety of raw materials and sustainable development. Biomass carbon materials are mainly artificial and natural non-fossil materials, mainly including plants, agricultural products and by-products. The use of biomass to prepare carbon materials not only reduces environmental pollution, but also greatly reduces production costs. Starch, due to its unique pore structure, makes it possible to apply it to electrochemical energy storage. Heteroatom doping is a common and effective method to change the lithium storage capacity of carbon structure.

[0004] At present, there is an urgent need to develop a lithium-ion battery negative electrode with better cycle performance and rate performance. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a boron quantum dot and starch carbon composite and a preparation method and application thereof. The composite material has good lithium storage capacity, and its long cycle performance and rate performance under large current test conditions are better than those of starch carbon materials, thereby achieving improved electrochemical performance and further expanding the application scope of boron quantum dots.

[0006] To this end, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing a boron quantum dot and starch carbon composite in an optional embodiment, comprising the following steps: The starch and ammonium pentaborate are mixed, added into the boron quantum dot solution and stirred, and then subjected to a hydrothermal reaction, and finally dried and annealed to obtain a boron quantum dot and starch carbon composite; Wherein, the mass ratio of the starch to ammonium pentaborate is 1:0.3-1.

[0007] The present invention fully mixes starch, ammonium pentaborate and boron quantum dot solution, and then uses high temperature annealing to realize the compounding of boron quantum dots and starch carbon. By adding ammonium pentaborate, the present invention can make the composite form a wrinkled spherical structure, further enhance the lithium ion adsorption and improve the lithium storage performance of the electrode material.

[0008] Preferably, the mass volume ratio of the starch and the boron quantum dot solution is 1 g: 0-30 mL.

[0009] Preferably, the hydrothermal reaction time is 6-8 hours; and / or, the hydrothermal reaction temperature is 150-200°C. The stirring time is 10-12 hours. The drying time is 8-12 hours; and / or, the drying temperature is 60-100°C. The annealing time is 1-3 hours; and / or; the annealing temperature is 600-1000°C. The annealing is carried out under a protective gas atmosphere; the protective gas is selected from one or more of nitrogen, argon or helium.

[0010] In a second aspect, the present invention provides, in an optional embodiment, a boron quantum dot and starch carbon composite, which is prepared by the above-mentioned preparation method.

[0011] In a third aspect, the present invention provides, in an optional embodiment, a use of the above-mentioned boron quantum dots and starch-carbon composite as a negative electrode material for a lithium-ion battery.

[0012] In a fourth aspect, the present invention provides a lithium-ion battery in an optional embodiment, comprising a positive electrode material, a negative electrode material, a separator and an electrolyte; the negative electrode material comprises the above-mentioned boron quantum dots and starch-carbon composite.

[0013] In the present invention, the material of the positive electrode is selected from one of ternary nickel-cobalt-manganese, lithium manganate, lithium iron phosphate, ternary nickel-cobalt-manganese or ternary nickel-cobalt-aluminum, the material of the diaphragm is selected from one of polypropylene, polyethylene, a composite of polypropylene and polyethylene, ceramic, glass fiber or cellulose, the electrolyte used can be a conventional electrolyte, the electrolyte includes a solvent and a lithium salt; further, it can also include additives; wherein the lithium salt can be any one of lithium perchlorate, lithium hexafluorophosphate, and lithium tetrafluoroborate, the solvent can be at least one of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC), and the additive can be anisole and / or carbodiimide compounds, etc.

[0014] Compared with the prior art, the present invention has one of the following beneficial effects: 1. The boron quantum dots and starch-carbon composite provided by the present invention have good lithium storage capacity, and the long cycle performance and rate performance under large current test conditions are better than those of starch-carbon materials, thereby achieving improved electrochemical performance and further expanding the application scope of boron quantum dots.

[0015] 2. The synthesis of the boron quantum dots and starch-carbon composite material provided by the present invention is relatively simple, the raw material cost is low, and it is conducive to large-scale production.

[0016] 3. The boron quantum dots and starch carbon composite provided by the present invention form BC x O 3-xThe structure increases the number of hole-type carriers and changes the electrical neutrality of the material, thereby enhancing the electrical conductivity and electron mobility of the composite material.

[0017] 4. The boron quantum dots and starch-carbon composite provided by the present invention improve the pore structure, increase the specific surface area, shorten the ion diffusion length, and enhance the electrochemical performance. Boron quantum dots increase the number of hole-type carriers and change the electrical neutrality of the material, thereby enhancing the conductivity and electron mobility of the composite.

[0018] 5. The preparation method of the present invention is simple, low-cost, and has abundant resources, which is conducive to large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 This is a schematic diagram of the process of preparing boron quantum dots and starch-carbon composites according to Example 1 of the present invention; Figure 2 This is a long cycle performance diagram of the negative electrode materials prepared in Example 9 of the present invention and Comparative Examples 1-3 at a current density of 2 A / g; Figure 3 This is a long cycle performance diagram of the negative electrode materials prepared in Comparative Examples 4 and 5 of the present invention at a current density of 2 A / g; Figure 4 The rate performance diagram of the negative electrode materials prepared in Example 9 of the present invention and Comparative Examples 1-3; Figure 5 This is a rate performance diagram of the negative electrode materials prepared in Comparative Examples 4 and 5 of the present invention; Figure 6 Schematic diagram of lithium ion diffusion coefficient of negative electrode materials prepared in Example 9 of the present invention and Comparative Examples 1-3 during discharge. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0022] The technical solution of the present invention will be further described below in conjunction with specific implementation methods.

[0023] Example 1: Combination Figure 1 This embodiment provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: Weigh 1.53g starch and 1.53g pentaboric acid amine, add them to the prepared boron quantum dot (provided by North University of China, the preparation method can refer to the content in Chinese invention patent CN201910555713.7) solution (15mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0024] Example 2: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: Weigh 1.53g starch and 1.53g pentaboric acid amine, add them to the prepared boron quantum dot solution (20mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0025] Example 3: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: Weigh 1.53g starch and 1.53g pentaboric acid amine, add them to the prepared boron quantum dot solution (30mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0026] Example 4: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: 1.53 g starch and 0.77 g pentaboric acid amine were weighed and added to the prepared boron quantum dot solution (15 mL). After being fully stirred for 12 h, the solution became milky white and was then placed at 180 ° C for hydrothermal reaction for 6 h. After the reaction was completed, the hydrothermal product was transferred to a clean evaporating dish and vacuum dried at 80 ° C in a forced air drying oven for 10 h. After drying, the product was annealed at 800 ° C for 1 h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0027] Example 5: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: 1.53 g starch and 0.77 g pentaboric acid amine were weighed and added to the prepared boron quantum dot solution (20 mL). After being fully stirred for 12 h, the solution became milky white and was then placed at 180 ° C for hydrothermal reaction for 6 h. After the reaction was completed, the hydrothermal product was transferred to a clean evaporating dish and vacuum dried at 80 ° C in a forced air drying oven for 10 h. After drying, the product was annealed at 800 ° C for 1 h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0028] Example 6: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: Weigh 1.53g starch and 0.77g pentaboric acid amine, add them to the prepared boron quantum dot solution (30mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0029] Example 7: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: Weigh 1.53g starch and 0.53g pentaboric acid amine, add them to the prepared boron quantum dot solution (15mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0030] Example 8: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: Weigh 1.53g starch and 0.53g pentaboric acid amine, add them to the prepared boron quantum dot solution (20mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0031] Example 9: This example provides a method for preparing a boron quantum dot and starch carbon composite, comprising the following steps: 1.53 g starch and 0.53 g pentaboric acid amine were weighed and added to the prepared boron quantum dot solution (30 mL). After being fully stirred for 12 h, the solution became milky white and was then placed at 180 ° C for hydrothermal reaction for 6 h. After the reaction was completed, the hydrothermal product was transferred to a clean evaporating dish and vacuum dried at 80 ° C in a forced air drying oven for 10 h. After drying, the product was annealed at 800 ° C for 1 h under argon atmosphere to obtain a boron quantum dot and starch carbon composite, recorded as B dots@BC.

[0032] Comparative Example 1: This comparative example provides a method for preparing a starch-carbon composite, comprising the following steps: 1.53 g of starch was weighed and added to an isopropanol solution (30 mL). After being fully stirred for 12 h, the solution became milky white and was then placed at 180 °C for a hydrothermal reaction for 6 h. After the reaction was completed, the hydrothermal product was transferred to a clean evaporating dish and vacuum dried at 80 °C in a forced air drying oven for 10 h. After drying, the product was annealed at 800 °C for 1 h in an argon atmosphere to obtain a starch-carbon composite, recorded as PC.

[0033] Comparative Example 2: This comparative example provides a method for preparing a starch-carbon composite, comprising the following steps: 1.53 g starch and 0.53 g ammonium pentaborate were weighed and added to an isopropanol solution (30 mL). After being fully stirred for 12 h, the solution became milky white and was then placed at 180 °C for a hydrothermal reaction for 6 h. After the reaction was completed, the hydrothermal product was transferred to a clean evaporating dish and vacuum dried at 80 °C in a forced air drying oven for 10 h. After drying, the product was annealed at 800 °C for 1 h in an argon atmosphere to obtain a starch-carbon composite, recorded as BC.

[0034] Comparative Example 3: This comparative example provides a method for preparing boron quantum dot-doped starch carbon material, comprising the following steps: 1.53 g of starch was weighed and added to the prepared boron quantum dot solution (30 mL). After being fully stirred for 12 h, the solution became milky white and was then placed at 180 ° C for a hydrothermal reaction for 6 h. After the reaction was completed, the hydrothermal product was transferred to a clean evaporating dish and vacuum dried at 80 ° C in a forced air drying oven for 10 h. After drying, the product was annealed at 800 ° C for 1 h under an argon atmosphere to obtain a starch-carbon composite, recorded as B dots@C.

[0035] Comparative Example 4: This comparative example provides a method for preparing a boron quantum dot-doped starch carbon material, comprising the following steps: Weigh 1.53g starch and 0.3g pentaboric acid amine, add them to the prepared boron quantum dot solution (30mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0036] Comparative Example 5: This comparative example provides a method for preparing a boron quantum dot-doped starch carbon material, comprising the following steps: Weigh 1.53g starch and 1.68g pentaboric acid amine, add them to the prepared boron quantum dot solution (30mL), stir thoroughly for 12h, the solution becomes milky white, and then place it at 180℃ for hydrothermal reaction for 6h. After the reaction is completed, transfer the hydrothermal product to a clean evaporating dish and vacuum dry it at 80℃ in a forced air drying oven for 10h. After drying, the product is annealed at 800℃ for 1h under argon atmosphere to obtain a boron quantum dot and starch carbon composite.

[0037] Experimental Example: The negative electrode material, conductive agent (acetylene black) and binder (PVDF) prepared in Example 9 and Comparative Examples 1-5 were poured into a clean agate mortar at a mass ratio of 8:1:1 and ground to obtain a battery negative electrode. Then, a battery positive electrode (LiFePO4), a battery negative electrode, a separator (Whatman GF / D type) and an electrolyte (1 mol / LLiPF6 EC:DEC=1:1, vol, 10% FEC) were assembled into a lithium-ion battery. The cycle performance, rate performance and lithium ion diffusion coefficient of the lithium-ion battery during discharge were tested at a current density of 2 A / g. The results are shown in Figure 2-Figure 6 .

[0038] pass Figure 2-Figure 6 It can be seen that: Figure 2Among them, the B dots@BC electrode has the highest initial reversible capacity and the best cycle stability, and the reversible capacity remains at 238 mAh / g after 1000 cycles. The charge and discharge capacities at 100, 500 and 1000 cycles are 234 / 234 mAh / g, 223 / 223 mAh / g and 238 / 238 mAh / g, respectively, and the Coulombic efficiency is maintained at 100%. This further shows that the electrochemical reaction of the B dots@BC electrode is highly reversible. The reversible capacity of the B dots@C electrode is only 163 mAh / g after 1000 cycles. For BC and PC, the capacity of the BC electrode remains at 148 mAh / g after 1000 cycles, while the PC electrode only shows a reversible capacity of 65 mAh / g after 1000 cycles, indicating that boron doping causes an increase in edge defects and provides more redox active sites, which ensures high capacity and efficient lithium ion storage. Figure 3 In the embodiment 4-5, the amount of ammonium pentaborate added was set to 0.3 g and 1.68 g, named B dots@BC0.3 and B dots@BC 1.68. It can be seen from the figure that the cycle capacity of the two is basically the same. After 100 cycles, the charge and discharge capacities are 168 / 168 mAh / g and 163 / 164 mAh / g, respectively. After 500 cycles, the charge and discharge capacities are 248 / 249 mAh / g and 246 / 246 mAh / g, respectively. Compared with the B dots@BC prepared in Example 9, the cycle capacity of B dots@BC 0.3 and Bdots@BC 1.68 is lower in the first 200 cycles. This is because the change in the amount of ammonium pentaborate added requires more cycles to activate the boron quantum dots. Figure 4 In the experiment, the B dots@BC electrode showed excellent rate performance. When the current density increased from 0.1 A / g to 10.0 A / g, the corresponding capacities of B dots@BC were 868, 351, 255, 228, 196 and 156 mAh / g, respectively. After high current cycling, when the current density returned to the initial 0.5 A / g, the electrode still achieved a high capacity of 318 mAh / g, showing good structural stability. At the same time, the BC electrode showed specific capacities of 869, 326, 255, 227, 169 and 130 mAh / g at current densities of 0.1, 0.5, 1.0, 2.5, 5.0 and 10.0 A / g, which was much higher than that of the PC electrode. This shows that the incorporation of boron is beneficial to the migration of ions and plays a key role in improving rate performance. Figure 5In the comparison, the B dots@BC 0.3 and B dots@BC 1.68 prepared by the method in Example 9 have a specific capacity of 564, 154, 123, 93, 70, 45 mAh / g and 524, 177, 144, 110, 87, 65 mAh / g at current densities of 0.1, 0.5, 1.0, 2.5, 5.0 and 10.0 A / g, respectively. By comparing B dots@BC, it can be found that the rate performance has decreased, indicating that the amount of ammonium pentaborate added has a direct effect on the rate performance. Figure 6 The lithium ion diffusion coefficient of B dots@BC is between 0.5 × 10 -12 cm 2 / s and 1.6 ×10 -9 cm 2 / s, during the charging process, the B dots@BC electrode exhibits a high lithium ion diffusion coefficient in the entire voltage window.

[0039] Although the principles of the present invention are described in detail above in conjunction with the preferred embodiments of the present invention, those skilled in the art should understand that the above embodiments are merely explanations of the exemplary implementations of the present invention, and are not intended to limit the scope of the present invention. The details in the embodiments do not constitute limitations on the scope of the present invention, and any obvious changes such as equivalent transformations, simple replacements, etc. based on the technical solution of the present invention, without departing from the spirit and scope of the present invention, fall within the protection scope of the present invention.

Claims

1. A method for preparing a boron quantum dot and starch carbon composite, characterized in that: The following steps are involved: After starch and ammonium pentaborate are mixed, they are added to the boron quantum dot solution and stirred, followed by a hydrothermal reaction, and finally dried and annealed to obtain a boron quantum dot and starch carbon complex. The role of adding ammonium pentaborate is to pre-boronate the starch to form a wrinkled spherical structure and increase the reaction sites. The spherical structure can also be constructed by adding boric acid; Wherein, the mass ratio of the starch to ammonium pentaborate is 1:0.3-1.

2. The method for preparing the boron quantum dots and starch-carbon composite according to claim 1, characterized in that: The mass volume ratio of the starch and the boron quantum dot solution is 1g:15-30mL.

3. The method for preparing the boron quantum dots and starch-carbon composite according to claim 1, characterized in that: The hydrothermal reaction time is 6-8 hours; and / or, The temperature of the hydrothermal reaction is 150-200°C.

4. The method for preparing the boron quantum dots and starch-carbon composite according to claim 1, characterized in that: The stirring time is 10-12 hours.

5. The method for preparing the boron quantum dots and starch-carbon composite according to claim 1, characterized in that: The drying time is 8-12 hours; and / or, The drying temperature is 60-100°C.

6. The method for preparing the boron quantum dots and starch-carbon composite according to claim 1, characterized in that: The annealing time is 1-3 hours; and / or, The annealing temperature is 600-1000°C.

7. The method for preparing the boron quantum dots and starch-carbon composite according to claim 1, characterized in that: The annealing is carried out in an atmosphere of protective gas; The protective gas is selected from one or more of nitrogen, argon or helium.

8. A boron quantum dot and starch carbon composite, characterized in that: The preparation method is described in any one of claims 1 to 6.

9. Use of the boron quantum dots and starch-carbon composite according to claim 8 as a negative electrode material for lithium-ion batteries.

10. A lithium ion battery, characterized in that: Including positive electrode materials, negative electrode materials, separators and electrolytes; The negative electrode material comprises the boron quantum dots and starch-carbon composite according to claim 9.

Citation Information

Patent Citations

  • A method for preparing boron quantum dots and their applications

    CN110194464B